1991
DOI: 10.1159/000186377
|View full text |Cite
|
Sign up to set email alerts
|

Complete Seroconversion by Low-Dose Intradermal Injection of Recombinant Hepatitis B Vaccine in Hemodialysis Patients

Abstract: The present study was undertaken to find out if the seroconversion rate of hemodialysis (HD) patients was enhanced by the intradermal (i.d.) inoculation of recombinant hepatitis B (HB) vaccine. Thirty-five HBs-Ag, HBs-Ab and HBc-Ag, HBc-Ab negative HD patients were divided into three groups: 14 patients in group I received 5 μg HBs Ag i.d. every 2 weeks, 13 patients in group II were given 2.5 μg HBs vaccine i.d. every 2 weeks, 5 times, then every week. The remaining 8 patients in group III were immunised with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
(16 reference statements)
3
25
0
Order By: Relevance
“…Yet, they differ for primitive renal desease and clinical patholo gy related to their immune function, as for sensitivity to antiviral vaccination [1][2][3][4]. We suggested that they must not be regarded as a homogeneous group in these aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, they differ for primitive renal desease and clinical patholo gy related to their immune function, as for sensitivity to antiviral vaccination [1][2][3][4]. We suggested that they must not be regarded as a homogeneous group in these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…All were negative for infections and HBV markers of previous contact. Patients' renal pa thologies were: idiopathic CRF [4], primary CGN [3]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is important that patients with chronic renal failure be offered adequate protection against HBV when they enter a renal replacement therapy program. Because of the low seroconversion rate among chronic HD patients, multiple strategies have been used to enhance the immune response to HBV vaccination in these patients [12][13][14][15]. These include: doubling the vaccination dose (40 Ìg/dose in HD patients), use of intradermal versus intramuscular mode of injection [12,13], administration of the vaccine in the deltoid muscle, giving an additional booster dose, beginning the vaccination series before the patients reach end-stage renal disease, giving a booster dose (40 Ìg) when the antibody titer falls to !10 IU/ml, and finally, using various growth factors or adjuvants, e.g., recombinant human erythropoietin [13,14] and granulocyte-macrophage colony-stimulating factor (GM-CSF) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of anti-HBV vaccination in chronic uremia has been limited by the depressed immune re sponse, detectable since the early phases of renal failure [1], Many authors have proposed several strategies to overcome this poor response [1][2][3][4], We report here our experience with a two-step integrated protocol of anti-HBV vaccination, combining in sequence the intramuscular and the intrader mal routes of administration.…”
Section: Introductionmentioning
confidence: 99%